Photosynthesis in Isolated Chloroplasts of the Crassulacean Acid Metabolism Plant Sedum praealtum - Spalding, Martin H. (1980)
Intact chloroplasts were isolated from protoplasts of the Crassulacean acid metabolism plant Sedum praealtum D.C. Typical rates of CO(2) fixation or CO(2)-dependent O(2) evolution ranged from 20 to 30 micromoles per milligram chlorophyll per hour and could be stimulated 30 to 50% by several Calvin cycle intermediates. The pH optimum for CO(2) fixation was 7.0 to 7.6 with considerable activity as low as pH 6.4. Low concentrations of orthophosphate (Pi) (optimum 0.4 millimolar) stimulated photosynthesis while high concentrations (5 millimolar) caused some inhibition. Both CO(2) fixation and CO(2)-dependent O(2) evolution exhibited a relatively long lag phase (4 to 6 minutes) which remained constant between 0.4 to 5 millimolar Pi. The lag phase could be decreased by addition of dihydroxyacetone-phosphate or ribose 5-phosphate. Further results are presented which suggest these chloroplasts have a functional phosphate translocator. A long lag period at optimum Pi concentration, no effect of high Pi levels on the lag phase, lack of severe inhibition of photosynthesis by high Pi concentrations, and the relatively low pH optimum for photosynthesis are characteristics unlike those previously reported with chloroplasts of C(3) plants.